On-Line Analytical Processing (OLAP) as a Information Tool for Modern Management - Hanna Borzęcka (Contemporary Economics)
The article contains on question, what it is the wholesalers of data and what are the advantage from its initiating. It defines the actual information needs for management as well as it defines the part of wholesalers of data in satisfying these needs. It the conception of multidimensional structures of data, in the article formalize multidimensional model of data and basic structure wholesalers data are introduced, built according to authoressí own conception. It is the OLAP cube. Publication contains also the proposal of innovation and it forecasts the rise of new generation of wholesalers data for solving modern management problems.